Analisis Kelayakan Teknis dan Finansial Pengembangan Energi Arus Laut di Selat Madura - Firdaus, Adil Mahfudz; Kusumastanto, Tridoyo; Nurjaya, I Wayan (Universitas Brawijaya, Indonesia, 2014)
The increase number of the user of oil and gas energy will lead to depletion of fossil energy resources, therefore it is important to develop renewable energy sources. Ocean currents energy is one of renewable energy sources which can be developed to fulfill problems of the highly request of energy. The economic of ocean currents study has not been known clearly in the aspect of price and feasibility. Therefore, this research aims to analyze the potential of ocean currents energy development as a power plant in Madura Strait, East Java Province. The analysis methods that were used in this study were oceanographic, technical and benefit cost. Based on the research, Madura Strait has sufficient resource potential to produce energy. Benefit cost analysis shows that ocean currents energy power plant development is financially feasible to be developed for 2 units or more.